The Effect of Internal Control and Compliance with Accounting Rules on the Quality of Financial Statements at PT. Bank of North Sumatra Medan - Hasbiana Dalimunthe; Aditya Amanda Pane (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to examine the effect of internal control and compliance with accounting rules on the quality of financial reports at PT Bank Sumatera Utara (North Sumatra). This research uses associative method. The population in this study were three divisions in Bank SUMUT, namely the Accounting and Tax Division, the General Division and the Operations Division. The sample used in this study were 35 respondents. The data analysis technique in this research is data quality test which includes validity and reliability tests, classic assumption test which includes normality test, multicollinearity test, heteroscedasticity test, and hypothesis test which includes t test, determination test (R2) and multiple linear regression test.